Novel Gradient Elution (U)HPLC Method Development that Enables Successful Method Transfer - Protić, Ana; Milenković, Milan; Rašević, Marija; Otašević, Biljana; Zečević, Mira; Krmar, Jovana; Malenović, Andjelija (Archives of Pharmacy, 2022)
Nowadays, one of the ultimate requirements in drug analysis is rapid method development, prompt chromatographic run time and long lasting method’s lifecycle. Special attention should be paid to development of gradient elution (U)HPLC methods that are commonly related to troubleshooting during the inter-laboratory method transfer. The dwell volume difference between (U)HPLC systems is the main reason for this issue. The aim of this study was to propose new gradient method development methodology with integrated dwell volumes values in the optimization process. This is especially useful approach for industry where is frequently known which (U)HPLC instruments will be applied for drug analysis. Proposed methodology was tested on the model mixture which encompassed dabigatran etexilate mesylate and its nine impurities. Experimental design methodology and three different (U)HPLC instruments with significant dwell volume differences were utilized. Statistically significant variables were selected with Plackett-Burman design, and along with dwell volume values were included in D-optimal design. The separation criteria s between adjacent peaks was selected as output for method optimization. Indirect modelling together with Monte Carlo simulations enabled selection of optimal and robust chromatographic conditions joint for all instruments. The optimal conditions included 24% (v/v) of initial amount of acetonitrile, 54% (v/v) of the final amount of acetonitrile, 15 min of gradient elution run time and pH value equal to 4.9. The proposed method utility was proved since it was successfully validated and met all validation criteria.